PENDIDIKAN BERWAWASAN GLOBAL DAN BERBASIS AGAMA - Mohamad Aminudin (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
Education is the guidance or help given by adults to the development of children to achieve their maturity with the aim that the child is capable enough to perform his own life duties do not depend on another person. Islamic education should be directed to the needs and changes of globalization era society. A global insightful education is an educational process designed to prepare students with the basic intellectual skills and responsibilities to enter a competitive life and with a degree of interdependence between nations. The current globalization in Islamic education can create a paradox or a symptom of counter morality, the conflict of two moral visions in a dianetral basis. The main challenges of globalization are: the advancement of science and technology, democracy, and the cultural field.